Motivasi Belajar Mahasiswa Program Studi Tadris Bahasa Inggris Institut Agama Islam Negeri Takengon - Sari, Rahmahidayati (Malewa: Journal of Multidisciplinary Educational Research, 2023)
This study aims to look at the learning motivation of TBI IAIN Takengon students. Learning motivation is directly related to the enthusiasm for learning. The research method chosen in this research is descriptive qualitative research using the research instrument is observation. The informants of this study were students of English Tadris at IAIN Takengon. The data analysis technique uses the Miles and Huberman approach using 3 steps, namely: reduction, display and verification. The conclusion of this study is that most students give their assignments on time, although there are some students who do not give assignments according to the agreed schedule. There are still students who are late or don't even attend online lectures. Most of the students seem to pay attention to the material taught by the lecturer. So it can be said that the learning motivation of TBI IAIN Takengon students is quite good.